La pedagogía de Santo Tomás ante una educación sin maestros (2014)
Acedia is understood as the activity of a man in state of depression, as he does not like anything he is doing; it is the more notorious effect of depersonalization. In order to examine if, in our society, we can observe this acedia, this article focuses its attention towards a nuclear area of human life: education. When does the teaching vocation simply moved to a simple paid work? Why should we make efforts for students to learn? These questions are the object of this article and the answers will be analyzed based on the thought of St. Thomas Aquinas. In this regard, the article is divided in two parts; on the one hand, it investigates the characterization of acedia and its role in the student’s training and, on the other hand, it researches on the role of the teacher once he/she was depersonalized. The paper concludes that the lack of meaning is behind any pedagogical strategy that promotes education and, therefore, it is necessary to return home (personalize) in order to be conscious of the vocation received and thus, educate.